The Features of the Organization and Perception of Teamwork by Students in Distance Learning - E.B. Atrushkevich (Психолого-педагогические исследования)
The article explores the features of organizing teamwork among students in the context of distance learning. The research involves an analysis of the challenges faced by both students and teachers when working in teams. An ascertaining experiment is presented, during which the experimental group received detailed instructions on organizing teamwork, which led to improved learning outcomes compared to the control group. Additionally, a study was conducted to examine students' perception of teamwork in the "Digital Forest Pedagogy" distance learning course. A total of 56 second-year students from the Higher School of Technology and Energy of SPbSUITD participated in the survey. The analysis revealed that students perceive teamwork as more complex compared to working in pairs, their assessment is influenced by prior experience. Issues related to responsibility and self-discipline, coordination and collaboration, as well as communication and feedback, were identified as the most problematic aspects.